REDUCTION OF THE LEVELS OF ANXIETY IN THE EMPLOYEES OF THE BINATIONAL ITAIPU, PRACTICING OF HYDROGIMNASTIC IN THE ACADEMY OF SWIMMING AQUAZUL OF FOZ DO IGUAÇU - PARANÁ (Fiep Bulletin - online, 2014)
The objectives of this study had been: To contribute in the improvement of the quality of life of the anxious employees of the Binational Itaipu, through a guided program of hydrogimnastic; To verify the anxiety levels and to prevent psychosomatic illnesses; To elaborate an adequate program of hydrogimnastic to the participants of the study; To verify if had improvement in the quality of life of the employees through thehydrogimnastic. For modernity and existing technology in the great companies we are suffering males day to day as the anxiety, stress, the muscular lack of motivation, depressions, pains and illnesses to articulate, that they cause to the lack in the work and damages to the company. Currently, the hydrogimnastic studied in the world all and futuristic already point the water as half the most propitious one with respect to the practical one of physical activities and affirm to be it white it of bigger investments in the financial market of fitness for the next years. The research was of the descriptive type, the instrument of collection of data was the questionnaire. 10 employees of the masculine and feminine sex of the Binational Itaipu of intentional form had been chosen. In the treatment of the data form was used for, through qualitative analysis of the data, to verify clinical registers of anxiety, depression, stress, etc. Through the descriptive questionnaire was verified between the I and II the evaluation differences and results. The hydrogimnastic work was of utmost importance for employees of the Binational Itaipu. Through the results it was evidenced that it had diverse aspects influenced for the hydrogimnastic work, as socialization, reduction of the fatigue, reduction of the anxiety that was the main objective, among others factors that had directly influenced the life of the employees, its performance and income inside of the company.